(untitled) (Journal of Plant Disease Sciences, 2020)
The young leaves of papaya plants showing mosaic, leaf distortion and shoe string symptoms were collected from the field of Department of Horticulture of Dr. PDKV, Akola. The virus inoculum was mechanically inoculated on 10 young healthy seedlings of papaya cv. Honeydew by conventional leaf rub method. After mechanical/ sap inoculation, initial upward rolling of leaves, mosaic, leaf distortion, shoe string symptoms were developed on all inoculated plants during incubation period of 12 to 15 days which were identical to the symptoms observed in the field. The host range of the papaya ringspot virus was found in the members of families Cucurbitaceae and Chenopodiaceae. Papaya ringspot virus was successfully produced mosaic, leaf distortion symptoms on leaves of Citrullus fistulosus (Tinda); mild mosaic, mild leaf distortion symptoms on Citrullus lanatus (Watermelon) and red nectrotic local lesions with white center on Chenopodium amaranticolor L. Papaya ringspot virus could not produce any symptoms on the plant species belonging to the families Amaranthaceae, Solanaceae, Leguminosae, Compositae and Balsaminaceae. Plants species belonging to the family Cucurbitaceae viz., Cucumis sativus L. (Cucumber), Cucumis melo L. (Muskmelon), Cucurbita moschata (Pumpkin), Luffa acutangula L. (Ridge gourd), Luffa cylindrica L. (Smooth gourd), Lagenaria ciceraria (Bottle gourd), Momordica charantia L. (Bitter gourd) and to the family Chenopodiaceae viz. Chenopodium murale used in host range study could not produce symptoms of papaya ringspot virus.